2022
DOI: 10.3389/fmed.2021.780196
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Concentration and Post-Operative Delirium in Elderly Patients Undergoing Femoral Neck Fracture Surgery

Abstract: This study aimed to determine the relationship between hemoglobin (Hb) concentration and post-operative delirium (POD) in elderly patients undergoing femoral neck fracture (FNF) surgery and to investigate whether the change in Hb concentration is associated with POD and the risk factors for POD. A total of 889 patients admitted with FNF between January 2016 and December 2020 were enrolled in this single-center, retrospective, case–control study. Hb concentrations were determined at admission and post-operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In a recent retrospective analysis, the authors underscored a notable link between diminished pre-operative Hb concentrations and significant fluctuations in Hb levels, indicating an elevated risk of postoperative delirium. Furthermore, factors such as advanced age, a history of stroke, transfer to the ICU postoperatively, and experiencing pain within the initial 2 days following surgery exhibited noteworthy associations in this study [92].…”
Section: Malnutrition and Anemiamentioning
confidence: 54%
“…In a recent retrospective analysis, the authors underscored a notable link between diminished pre-operative Hb concentrations and significant fluctuations in Hb levels, indicating an elevated risk of postoperative delirium. Furthermore, factors such as advanced age, a history of stroke, transfer to the ICU postoperatively, and experiencing pain within the initial 2 days following surgery exhibited noteworthy associations in this study [92].…”
Section: Malnutrition and Anemiamentioning
confidence: 54%
“…Severe pain, both preoperative and postoperative, may increase stress and the occurrence of POD in patients ( Ding et al, 2021 ; Liu et al, 2022 ). The higher the degree of pain, the higher the incidence of POD, which might be related to the fact that pain can significantly affect sleep and disrupt the sleep-wake cycle in the patient, thus impairing cognitive function ( Jaiswal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the results of the multifactorial logistic regression analysis showed that both pre‐op Hb and pre‐op RBC were associated with the development of delirium in the patients, and we found that this result could be due to the multicollinearity of these two factors through the analysis of multicollinearity. At the same time, previous studies have shown that Hb 50,51 and delirium are more strongly correlated than RBC 52 . Therefore, to avoid affecting the performance of the model and to improve the accuracy of the prediction model, we finally chose to include pre‐op Hb in the prediction model and exclude pre‐op RBC.…”
Section: Discussionmentioning
confidence: 99%